Use of the Earth Remote Sensing data for the monitoring of the level of soil fertility - Kabzhanova, G.R.; Baktybekov, K.S.; Kabdulova, G.A.; Aimbetov, A.A.; Aligazhiyeva, L.R. (Fundamental and Experimental Biology, 2020)
Ground monitoring of soil massifs takes a lot of time, labor force and material resources, yet is the most accurate and detailed method. When implementing complex methods for monitoring the soil cover, inclusion of space technologies is necessary. Remote sensing data carry objective information over the large areas. The article discusses the possibility of using remote sensing data for mapping and monitoring changes in the soil cover of Northern Kazakhstan. Based on thematic processing of remote sensing data of domestic satellites, spatial analysis of the content of main nutrients was executed in the sowing layer of soils, the relationship was revealed between fertility indicators and the value of vegetation indices for testing ground on the territory of Northern Kazakhstan. Remote sensing methods which are gaining more practical application in determination of qualitative changes in the state of the Earth’s surface are considered in this article. The use of remote sensing data enables developing automatic soil recognition and analysis systems for the quantitative assessment of soil variability. The use of remote sensing data of high and medium resolution, along with geoinformation technologies reveals great potential in assessing soil fertility, which contributes to the effective management of land resources, the preservation and maintenance of soil fertility.